2012
DOI: 10.1371/journal.pone.0044698
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Suppression of Early Phase of Adipogenesis by Microsomal PGE Synthase-1 (PTGES1)-Produced PGE2 and Aldo-Keto Reductase 1B3-Produced PGF2α

Abstract: We recently reported that aldo-keto reductase 1B3-produced prostaglandin (PG) F2α suppressed the early phase of adipogenesis. PGE2 is also known to suppress adipogenesis. In this study, we found that microsomal PGE2 synthase (PGES)-1 (mPGES-1; PTGES1) acted as the PGES in adipocytes and that PGE2 and PGF2α synergistically suppressed the early phase of adipogenesis. PGE2 production was detected in preadipocytes and transiently enhanced at 3 h after the initiation of adipogenesis of mouse adipocytic 3T3-L1 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
2
23
1
Order By: Relevance
“…The increased production of PGF 2 α and PGE 2 in the early phase of adipogenesis is a consequence of the elevated expression of the COX-2 gene [61]. PGF 2 α forms a positive feedback loop that coordinately suppresses the early phase of adipogenesis through the increased production of antiadipogenic PGF 2 α and PGE 2 , both of which inhibit PPAR γ function.…”
Section: Synergistic Suppression Of Early Phase Of Adipogenesis Bymentioning
confidence: 99%
See 1 more Smart Citation
“…The increased production of PGF 2 α and PGE 2 in the early phase of adipogenesis is a consequence of the elevated expression of the COX-2 gene [61]. PGF 2 α forms a positive feedback loop that coordinately suppresses the early phase of adipogenesis through the increased production of antiadipogenic PGF 2 α and PGE 2 , both of which inhibit PPAR γ function.…”
Section: Synergistic Suppression Of Early Phase Of Adipogenesis Bymentioning
confidence: 99%
“…Moreover, when the cells are caused to differentiate into adipocytes in medium containing both PGF 2 α and PGE 2 , the expression of the adipogenic genes is decreased to a greater extent than when the cells are cultured in a medium containing either of them. Thus, PGE 2 and PGF 2 α synergistically suppress the early phase of adipogenesis through a self-amplifying loop, triggered by PGF 2 α -FP receptor and PGE 2 -EP4 receptor couplings and activation of the COX-2 gene expression in 3T3-L1 cells [61]. …”
Section: Synergistic Suppression Of Early Phase Of Adipogenesis Bymentioning
confidence: 99%
“…The findings of higher expression of COX-1, AKR1B1, PTGES3, PTGIS, and PTGDS in omental versus subcutaneous adipose tissue as well as higher expression of COX-1, COX-2, AKR1B1, PTGES, and PTGDS in omental versus subcutaneous cultured preadipocytes are consistent with these results. Several studies previously established that the two COXs are the rate-limiting enzymes in the synthesis of PG [ 11 , 16 ]. In our study, higher expression of COX isoforms in visceral fat may explain depot differences in PG synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PTGES has been previously investigated in adipocytes [ 45 , 48 ], but the specific isoform involved in the production of PGE 2 has never been clearly identified in human adipose tissue. Fujimori et al recently demonstrated that PTGES is responsible for PGE 2 synthesis in 3T3-L1 cells [ 16 ]. Hétu and Riendeau demonstrated that expression of PTGES was greatly decreased in murine obese tissues, whereas PTGES2 and PTGES3 expression showed minor or no changes [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation